2016
DOI: 10.1080/01900692.2016.1186175
|View full text |Cite
|
Sign up to set email alerts
|

Popular Financial Reports as Fiscal Transparency Mechanisms: An Assessment Using the Fiscal Transparency Index for the Citizen User

Abstract: Popular financial reports (PFRs) are intended to increase transparency by providing financial information to a non-technical, citizen audience. We examine the extent to which PFRs are meeting the goal of transparency by developing a 23-criteria fiscal transparency index for the citizen user (FTI-CU) and applying it to a sample of PFRs (popular annual financial reports and citizen-centric reports) issued by local governments in the U.S. These criteria are organized into five areas: comprehension, access, financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 27 publications
(57 reference statements)
1
27
0
10
Order By: Relevance
“…It is based on the assumption that average citizens find typical governmental financial statements too long, complicated, and confusing [44]. It is mainly diffused in North-America (the US and Canada in particular), and the scholarly interest in the topic has been limited so far (for notable exceptions see [8,29,52,53].…”
Section: Popular Financial Reportingmentioning
confidence: 99%
“…It is based on the assumption that average citizens find typical governmental financial statements too long, complicated, and confusing [44]. It is mainly diffused in North-America (the US and Canada in particular), and the scholarly interest in the topic has been limited so far (for notable exceptions see [8,29,52,53].…”
Section: Popular Financial Reportingmentioning
confidence: 99%
“…Guidelines from citizen focus groups conducted by Yusuf and Jordan () identified newspaper‐level readability as appropriate for a citizen audience. The fiscal transparency index developed by Jordan et al () characterized comprehension needs for the lay audience of financial reports as being readability below 10th grade level. Yusuf and Jordan () tested this comprehension level using a student laboratory and found that more than 52 percent of laboratory participants found the readability of a sample report written at approximately 10th grade level to be “just right.” In contrast, 22 percent and 26 percent found it simplistic or complicated, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Popular financial reports, defined as financial reports distributed to citizens and other interested parties who lack a background in public finance but who need or desire a less detailed overview of the government's financial activities (Yusuf and Jordan ), have the explicit purpose of targeting the citizens and increasing their understanding of financial information. Analysis by Jordan et al () of popular reports as tools for fiscal transparency found that these reports meet many of the accessibility criteria used to assess MD&As.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…The literature on popular financial reporting highlights various topics. Therefore, this report can influence the non-financial information and the social value that intangibles acquire on the territorial context of reference (P. Biancone et al, 2016Groff & Pitman, 2004;Jordan, Yusuf, Berman, & Gilchrist, 2017;J.-E. Yusuf, Jordan, Neill, & Hackbart, 2013;J.-E. W. Yusuf & Jordan, 2012).…”
Section: Introductionmentioning
confidence: 99%